2021
DOI: 10.1101/2021.04.27.21255937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real world evidence of calcifediol use and mortality rate of COVID-19 hospitalized in a large cohort of 16,401 Andalusian patients

Abstract: Background: COVID-19 is a major worldwide health problem because of acute respiratory distress syndrome, and mortality. Several lines of evidence have suggested a relationship between the vitamin D endocrine system and severity of COVID-19. Methods: We present a retrospective survival study that includes all Andalusian patients hospitalized between January and November 2020 because of COVID-19 infection. Based on a central registry of electronic health records (the Andalusian Population Health Database, BPS), … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This has allowed to detect small differences in outcomes after adjusting for multiple covariates. Our study also differs from that of Loucera et al, a study that compares COVID-19 inhospital mortality in patients under vitamin D supplementation with unsupplemented, propensity score-matched, hospitalized COVID-19 patients, since it only analyzed hospitalized patients and not all the population at risk [38].…”
Section: Discussionmentioning
confidence: 79%
“…This has allowed to detect small differences in outcomes after adjusting for multiple covariates. Our study also differs from that of Loucera et al, a study that compares COVID-19 inhospital mortality in patients under vitamin D supplementation with unsupplemented, propensity score-matched, hospitalized COVID-19 patients, since it only analyzed hospitalized patients and not all the population at risk [38].…”
Section: Discussionmentioning
confidence: 79%
“…However, numerous observational studies and open‐label, RCTs have demonstrated a substantial relationship between vitamin D and COVID‐19 ( Table 1 ). 52 , 59 , 62 , 67 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 …”
Section: Vitamin D and Covid ‐19: Summary Of The E...mentioning
confidence: 99%
“…They found that the need for admission to the ICU was much lower in the group treated with VD (2%) compared to standard treatment (50%) [ 164 ]. The retrospective study carried out by Loucera et al, 2021, which concluded that patients who had adjusted their serum levels of 25(OH)D, for other health objectives, within the 15–30 days prior to hospitalization, presented better response to COVID-19 and increased survival [ 165 ]. Another cross-sectional study in 508 patients, conducted by Vasheghani et al, 2021, reported that mortality from COVID-19 had a negative correlation with the serum level of 25(OH)D and in those patients who were hospitalized, low levels of 25(OH)D, were associated with more severe disease and increased ICU admissions [ 162 ].…”
Section: Interaction Covid-19 and Multiple Sclerosismentioning
confidence: 99%